Turning Cancer Immunotherapy to the Emerging Immune Checkpoint TIGIT: Will This Break Through the Limitations of the Legacy Approach? - Haozhe Cui; Eyad Elkord (Vaccines)
The discovery of immune checkpoints (ICs) has pushed cancer treatment into the next era. As an emerging immune checkpoint, the TIGIT/CD155 axis inhibits the cytotoxicity of T and NK cells through multiple pathways. Immune checkpoint inhibitors (ICIs) targeting TIGIT are hopefully expected to address the issue of unresponsiveness to anti-PD-(L)1 monoclonal antibodies (mAbs) by combination therapy. This paper presents insights on the expression, structure and mechanism of action of TIGIT, as well as the principles and methods of designing mAbs targeting TIGIT and their clinical data. The advantages and disadvantages of targeting TIGIT using mAbs, bispecific and tri-specific antibodies (bsAbs and tsAbs), peptides, and compounds, in addition to potential combination therapies of anti-TIGIT with anti-PD-1 or cancer vaccines, are addressed. Finally, perspectives on current immunotherapies targeting TIGIT are discussed.